Immunization with a low-dose replicon DNA vaccine encoding Phl p 5 effectively prevents allergic sensitization - Gabler, Maximilian; Scheiblhofer, Sandra; Kern, Kerstin; Leitner, Wolfgang W.; Stoecklinger, Angelika; Hauser-Kronberger, Cornelia; Alinger, Beate; Lechner, Berta; Prinz, Monika; Vrtala, Susanne; Valenta, Rudolf; Thalhamer, Josef; et al. (Journal of Allergy and Clinical Immunology, 2006)
Replicase-based DNA vaccines stimulate T H1-biased immune responses at ultralow doses and induce self-removal of transfected cells through apoptosis. Both aspects are important requirements for efficient and safe DNA-based immunotherapy of type I allergies. A Sindbis virus replicon-based DNA vaccine encoding the major timothy grass pollen allergen Phl p 5 was evaluated for its antiallergic potential compared with a conventional DNA vaccine in a BALB/c mouse model of allergy. Mice were intradermally prevaccinated with plasmid DNA, followed by sensitization and intranasal allergen provocation with recombinant Phl p 5. In vitro proliferation and cytokine secretion was measured in splenocyte cultures. Distribution of IgG1, IgG2a, and IgE antibody subclasses was determined by means of ELISA. IgE-mediated degranulation was measured with the basophil release assay. Bronchoalveolar lavage fluid was analyzed for eosinophils, IL-4, IL-5, IL-13, and IFN-γ. Mucus production, inflammatory infiltrates, and epithelial damage were determined in lung sections. Both vaccines induced T H1-biased immune responses, resulting in suppression of functional IgE, reduction of eosinophilia in bronchoalveolar lavage fluid, and alleviation of lung pathology. However, immunization with the replicon DNA vaccine elicited these effects at a 100-fold lower dose compared with the conventional DNA vaccine. The increased immunogenicity of replicon-based DNA vaccines allows for application of extremely low doses, thereby eliminating the concerns associated with conventional DNA vaccines, which have to be administered at milligram amounts to induce immune reactions in human subjects. Their high safety profile makes replicon-based DNA vaccines promising candidates for treatment of type I allergies in the clinic.